How geoecological components of a terroir can be altered by spatial changes of vineyards – A case study from Eger Wine District (Hungary) - Novák, Tibor József; Hegyi, Balázs; Balogh, Szabolcs; Czímer, Bence; Rózsa, Péter (ERDKUNDE, 2023)
Terroir is a concept referring interactions of natural (topography, lithology, climate, soil etc.) and human (economic conditions, traditions, cultivation practices, etc.) factors; therefore, terroir is spatially delimited and subjected to environmental, socio-economic, and temporal changes. The geoecological background of wine districts are considered more stable among them, but, because of its natural diversity and the spatial changes of production sites, changes in abiotic terroir components might occur too. In this study the spatial changes of grape production sites in Eger Wine District (Hungary) across two and a half centuries (1784 to 2018), and their consequences on the composition of the geoecological factors (lithology, topography, soil characteristics) were analyzed. Modernization of cultivation, urbanization and increase of built-up areas around the central settlement resulted in decreased concentration, i.e. increased spatial dispersion to more remote vineyards further from Eger. It also has consequences on the lithological and topographical composition of the production sites. Besides the slightly increasing extent of vineyards (from 5346 ha to 7413 ha) we found a distinct decrease of vineyards at higher elevations and a substantial increase at lower elevations. Distribution according to slope gradient changed also remarkably, with the share of vineyards on <5  % slopes from 38  % to 65  %. These changes resulted in transformations of pedological characteristics according to the comparison of vineyard’s extent with soil map data: vineyards shifted to slightly acidic, more fertile (i.e. deeper soil layer with higher organic carbon content) soils. The share of vineyards with different lithology and parent material also changed: loose, calcareous Tertiary sediments decreased almost to half, and the share of vineyards over acidic volcanics and their weathered regoliths almost doubled. Comparing these two dominant lithological types and soil profiles derived from them, different pedological characters and taxonomic status were found (Phaeozems and Vertisols). However, comparison of these two lithological types based on main topsoil characteristics (pH, SOC, carbonates, depth of fertile soil layer, N, P, K content) according to 25 randomly chosen surficial soil samples at production sites, showed no significant differences.. In the case of this particular wine district, spatial changes of the production sites affected mostly the distribution by elevation, by slope gradient, but did not alter significantly the surface soil character of the terroir.